Progress in tear microdesiccate analysis by combining various transmitted-light microscope techniques. Issue 1 (December 2016) - Traipe-Salas, Felipe; Traipe-Castro, Leonidas; Salinas-Toro, Daniela; López, Daniela; Valenzuela, Felipe; Cartes, Christian; Toledo-Araya, Héctor; Pérez, Claudio; López Solís, Remigio
Abstract Background Tear desiccation on a glass surface followed by transmitted-light microscopy has served as diagnostic test for dry eye. Four distinctive morphological domains (zones I, II, III and transition band) have been recently recognized in tear microdesiccates. Physicochemical dissimilarities among those domains hamper comprehensive microscopic examination of tear microdesiccates. Optimal observation conditions of entire tear microdesiccates are now investigated. One-μl aliquots of tear collected from individual healthy eyes were dried at ambient conditions on microscope slides. Tear microdesiccates were examined by combining low-magnification objective lenses with transmitted-light microscopy (brightfield, phase contrasts Ph1, 2, 3 and darkfield). Results Fern-like structures (zones II and III) were visible with all illumination methods excepting brightfield. Zone I was the microdesiccate domain displaying the most noticeable illumination-dependent variations, namely transparent band delimited by an outer rim (Ph1, Ph2), homogeneous compactly built structure (brightfield) or invisible domain (darkfield, Ph3). Intermediate positions of the condenser (BF/Ph1, Ph1/Ph2) showed a structured roughly cylindrical zone I. The transition band also varied from invisibility (brightfield) to a well-defined domain comprising interwoven filamentous elements (phase contrasts, darkfield). Conclusions Imaging of entire tear microdesiccates by transmitted-light microscopy depends upon illumination. A more comprehensive description of tear microdesiccates can be achieved by combining illumination methods.